Cognitive behavioral therapy for insomnia in a military traumatic brain injury clinic: a quality improvement project assessing the integration of a smartphone application with behavioral treatment - Matsuura, Justin T.; Keller, Nicole S.; Lustik, Michael B.; Campbell, Carmen E.; Grills, Chad E. (Frontiers in Sleep, 2023)
Objectives: While the association between insomnia and traumatic brain injury (TBI) is well established, TBI rehabilitation programs that focus on sleep as a primary target are limited. Cognitive behavioral therapy for insomnia (CBTi) is an effective treatment for insomnia, however; its use within TBI clinics is relatively unknown. Therefore, our aim was to evaluate the implementation of CBTi, used in conjunction with a smartphone app for insomnia, within a US military TBI program to improve care within this setting. Setting: A TBI clinic at a US military installation. Methods: MHS beneficiaries underwent 6 sessions of CBTi and a 1-month post-treatment follow up session. Data was collected at each treatment session as part of routine clinical care. Results: A total of 69 US MHS beneficiaries seen at a TBI clinic with a diagnosis of insomnia began CBTi. Attrition rate at the end of the CBTi program and 1-month posttreatment session was 35% and 48%, respectively. Results demonstrated that sleep onset latency (SOL) and wake after sleep onset (WASO) decreased during treatment (p's < 0.001). Further, symptoms reported on the Insomnia Severity Index (ISI) improved during CBTi (p < 0.001). Conclusion: Findings demonstrate how CBTi used in conjunction with a CBTi smartphone application can be used to effectively treat insomnia for MHS beneficiaries seeking care for TBIs. This evaluation provides the basis for further research on how CBTi may improve care within TBI programs.